Sirius : a novel about the little dog who almost changed history - Crown, Jonathan, 1953- (Scribner, 2016)
"A highly original, tragicomic novel as seen through Sirius, an extraordinary dog who helps his Jewish family escape from Germany to California, becomes a Hollywood star, and, ultimately, contributes to Hitler's downfall"--